DETERMINASI PENERIMAAN DANA KREDIT PADA UMKM DI KECAMATAN KARAWANG TIMUR - Rosalina, Shinta; Lukita, Carolyn; Astriani, Devi (COMPETITIVE, 2024)
Indonesia's economic growth raises various challenges that must be faced by MSME workers. The majority of challenges faced by MSMEs are related to a lack of capital to develop their business, so they require financial support from financial institutions. The aim of this research is to find out whether the implementation of SAK EMKM, socialization of SAK EMKM, business size, and perceived usefulness have an influence on the receipt of credit funds. The method applied in the research is a quantitative approach. The population studied consisted of 3,157 MSMEs in East Karawang. The sample was selected purposively with 97 respondents who met certain criteria. The respondents who were the research subjects were MSMEs in East Karawang District, Karawang Regency. Data analysis was carried out using Partial Least Square Structural Equation Modeling (PLS-SEM) with the help of SmartPLS version 4.0. The model analyzed includes measurement and structural aspects, as well as hypothesis testing. The research results show that the implementation of SAK EMKM, business size, and perceived usefulness have a significant influence on the receipt of credit funds. However, the socialization of SAK EMKM has no influence on the receipt of credit funds for MSMEs.